2021
DOI: 10.1186/s11671-021-03526-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation on Cutting Mechanism in the Hybrid Machining Process of Single-Crystal Silicon

Abstract: In this paper, molecular dynamics simulations are carried out to investigate the cutting mechanism during the hybrid machining process combined the thermal and vibration assistants. A modified cutting model is applied to study the material removal behavior and subsurface damage formation in one vibration cycle. The results indicate that during the hybrid machining process, the dominant material removal mechanism could transform from extrusion to shearing in a single vibration cycle. With an increase of the cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 63 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…The deepest position of the damage is located below the abrasive, which means that the amorphous structure damage generated by the extrusion partly recrystallizes after the polishing. The recovery of generated damage was also reported by Xu et al [53].…”
Section: The Polishing Processsupporting
confidence: 80%
“…The deepest position of the damage is located below the abrasive, which means that the amorphous structure damage generated by the extrusion partly recrystallizes after the polishing. The recovery of generated damage was also reported by Xu et al [53].…”
Section: The Polishing Processsupporting
confidence: 80%
“…The hybrid machining technology could effectively inhibit subsurface damage. Molecular dynamics simulation in the in-situ laser and vibration hybrid assisted cutting of single crystal silicon have been carried out by Liu et al [185] through a modified molecular dynamics model, as shown in figure 22. They found that the introduction of the thermal field further reduced the cutting force based on UVC, and the thermal field could suppress the pull-off and cracking generated in UVC.…”
Section: Laser and Ultrasonic Vibration Assisted Cuttingmentioning
confidence: 99%
“…The Bridge Domain cross-scale transfer method (BD) was introduced. [19][20][21][22] Molecular dynamics theory was used to describe the selected area on the flank of the cutter tooth. And Lagrange method was used to describe the unselected area of flank of cutter tooth.…”
Section: Super-cell Model and Its Failure Criterion Of The Feature Po...mentioning
confidence: 99%